On bogey teams and circular triads: Psychological factors in team performance - Jan C. van Ours (Tinbergen Institute, 2025)
Team performance depends not only on the individual abilities of its members and cooperation between them but also on psychological factors such as confidence, rivalry, and perceived pressure. In a regular work environment, it is challenging to isolate the contribution of psychological factors. Analyzing sports data can be insightful, as performance metrics are widely available. This paper focuses on two phenomena that highlight the impact of psychological factors: bogey teams and circular triads. A "bogey team" refers to a team that consistently outperforms another team, often defying expectations. Circular triads involve non-transitive match outcomes among trios of teams. Using balanced panel data from the top league of Dutch football, the analysis identifies both bogey team relationships and circular triads in match outcomes. Clearly, psychological factors play a significant role in shaping team performance.
Keywords: C25; D01; Z2; 330; Non-transitivity; Circular triads; Bogey Teams; Football